Preoperative prediction of difficult laparoscopic cholecystectomy using a scoring system - Khetan, Ashish K.; Yeola, Meenakshi (International Surgery Journal, 2017)
Background: Laparoscopic cholecystectomy (LC) has become gold standard for the surgical treatment of gallbladder disease. 2% to 15% of patients require conversion to open surgery for various reasons. Pre-operative prediction of “difficult laparoscopic cholecystectomy” may not only improve patient safety but also be useful in reducing the overall cost of therapy. The aim of this study is to study the factors determining the preoperative predictability of difficult laparoscopic cholecystectomy. Method: 30 cases of laparoscopic cholecystectomy operated by a single experienced surgeon. There are total 15 score from history, clinical and sonological findings. They were evaluated and scored on the basis of scoring system of Randhawa and Pujahari. Score up to 5 is defined as easy, 6-10 as difficult and 11-15 as very difficult. Result: Previous history of hospitalization for cholecystitis and increased gall bladder wall thickness were found statistically significant in predicting difficult LC. Conclusion: The scoring system had a positive prediction value for easy prediction of 81.9% and for difficult prediction of 75%.